2018
DOI: 10.1007/s00167-018-5310-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of chronic proximal hamstring avulsion injuries using ipsilateral distal hamstring tendons results in good clinical outcomes and patient satisfaction

Abstract: Reconstruction of chronic proximal hamstring avulsion injuries using ipsilateral distal hamstring tendons results in good clinical outcomes and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…PHAT is one of the few validated outcome measures tailored to proximal hamstring tendon repair, as opposed to measures that apply to a broad scope of lower limb or musculoskeletal injuries. 11 PHAT was used in 4 studies 6,10,11,20 ; however, 2 of these were written by the same author, 10,11 which creates a risk of bias.Further research is needed to determine if PHAT should be implemented widely to evaluate outcomes in patients after proximal hamstring repair.…”
Section: Discussionmentioning
confidence: 99%
“…PHAT is one of the few validated outcome measures tailored to proximal hamstring tendon repair, as opposed to measures that apply to a broad scope of lower limb or musculoskeletal injuries. 11 PHAT was used in 4 studies 6,10,11,20 ; however, 2 of these were written by the same author, 10,11 which creates a risk of bias.Further research is needed to determine if PHAT should be implemented widely to evaluate outcomes in patients after proximal hamstring repair.…”
Section: Discussionmentioning
confidence: 99%
“…5 While most techniques involve use of Achilles tendon allograft, other grafts have been described. Ebert et al 14 reported a case series of 6 patients who underwent reconstruction of chronic proximal hamstring avulsion injuries using ipsilateral distal hamstring autograft. They noted good outcomes with improved strength and endurance as well as return to recreational and sporting activities.…”
Section: Discussionmentioning
confidence: 99%
“…The knee was positioned in 90 flexion for fixation to the ischial tuberosity, which was accomplished using 2 suture anchors. Others have similarly used only 2 to 3 suture anchors for attachment to the tuberosity such as in the previously cited series by Klingele and Sallay, Ebert, as well as Atzmon et al 9,13,14 However, as described in a study by Moatshe et al, 17 the use of 5 anchors is biomechanically stronger and more similar to native hamstring tendon strength. While this technique was used in repair of acute injuries, the use of 5 suture anchors may improve strength of chronic reconstructions as well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as will be described below, it can be used either with a bone plug, or as an all-soft tissue graft. Other graft options described in the literature include semitendinosus and gracilis autograft, obtained either from the ipsilateral [29] or contralateral [24] knee, and iliotibial band autograft [9].…”
Section: Graft Selectionmentioning
confidence: 99%
“…It is also the technique more familiar to most surgeons, since most acute repairs are performed in a similar manner. Many different anchor options have been described in the context of proximal hamstring repair, including PEEK [24,29] and bioabsorbable [27] implants. The anchors are inserted into the lateral aspect of the ischial tuberosity, 1 cm apart, and are incorporated into the repair as described below.…”
Section: Suture Anchorsmentioning
confidence: 99%